Kebiasaan Shalat Jumat di Sekolah sebagai Upaya Membentuk Disiplin pada Siswa Kelas Atas di Sekolah Dasar Tahfidz Ababil, Kota Pagar Alam - Nabila, Cahya; Palupi, Aisyah Putri Dea (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
This study aims to analyze the implementation of Friday prayer as a habitual effort to foster discipline among upper-grade students at Tahfidz Ababil Elementary School in Pagar Alam City, and to identify supporting and inhibiting factors. Using a descriptive qualitative method, data were collected through non-participant observation, structured interviews with supervising teachers and students, and documentation. Data analysis techniques refer to the Miles and Huberman model, including data reduction, data presentation, and conclusion drawing. The results show that the habitual Friday prayer at Tahfidz Ababil Elementary School in Pagar Alam City has proven effective in fostering discipline among students. Students demonstrated active participation, punctuality, and an understanding of the importance of worship. Teachers played a central role as guides and role models, consistently instilling the values of discipline. Key supporting factors included active student involvement, full teacher support, and synergy between parents and the community. However, inhibiting factors also existed, such as a lack of participation among some students, less serious behavior during worship, and sometimes a lack of teacher firmness in supervision. Nevertheless, this program overall contributed significantly to strengthening character education and the continuous instilling of religious values and discipline in students. Keywords: Friday Prayer Habits, Discipline, High School Students, Character Education